Lepidópteros tortricídeos em pomares de pomóideas e prunóideas da Beira Interior - Mexia, António (2003)
A survey for lepidoptera tortricid feeding on pome and stone fruit orchards was carried out, in 2002, in Beira Interior, Portugal. Adults were captured using sexual pheromones traps and visual observation techniques were used in larvae detection. The species monitorised were: Adoxophyes orana, Cacoecimorpha pronubana, Pandemis heparana, Pandemis ribeana(=cerasana), and Cydia molesta. Among the five species monitorised only Cacoecimorpha pronubana and Pandemis heparana were captured. Flight curves of these two species are shown in this paper. Although there were detected fruits and leaves with characteristic symptoms of attack of these species, larvae were not found, suggesting populations not economically significant.